Quality judgement of Indian hearing aids using hearing aid transduced speech discrimination - Ramani G (Journal of All India Institute of Speech and Hearing, 1970)
One hundred subjects with normal hearing and normal discrimination were tested using pure tones lind phonetically balanced monosyllables. Later, to study the effect of hearing aid  distortion in speech, jive popular Indian hearing aids wer~ chosen. Using controlled system .four equivalent list o/monosyllables were recorded through these hearing aids on a high fidelity tape recorder. It was then administered to the above subjects through the audiometer to find discrimination score. The difference between two discrimination scores was taken to rank the hearing aids in terms of their fidelity.